Identifying Effective Organizational Factors on Corporate Entrepreneurship in Tehran Municipality’s Department of Urban Services - Khakbaz, Peyman Pournasr; ., Behrouz Zarei (Information Management and Business Review, 2011)
the companies have realized the need for entrepreneurship and the entrepreneurial thoughts have penetrated in the administrative structures, because the growth, dynamics and survival of the modern organizations depends on the implementation of organizational entrepreneurship. Consequently, nowadays most of the organizations need organizational entrepreneurship development for growth and survival. The objective of the present paper is to fill the existing gap in the studies. The method of the research is a mixed one; in the qualitative stage, semi-structured and open interviews and investigation of related documents were used, and in the quantitative stage, the questionnaire was applied to gather data. In the researchâ€™s quantitative stage, a statistical population consisted of managers, employees of the case study were considered, and the simple random sampling method was used. In addition, in this stage, the questionnaires were used as the data collection tool and the experts in the qualitative stage measured the researchâ€™s validity, and the questionnaireâ€™s reliability was approved through Cronbachâ€™s alpha of 0.88. The mean analysis was applied in this stage for the data analysis. The findings of this paper shows that the effective organizational factors in organizational entrepreneurship in Tehran Municipality’s Department of Urban Services are categorizes in the seven issues of managerial support, availability of resources, reward systems, corporate culture, entrepreneurial strategies, and risk taking.